2017
DOI: 10.1016/j.pec.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

How physicians draw satisfaction and overcome barriers in their practices: “It sustains me”

Abstract: Fostering fully mature professional development among physicians will require new skills and opportunities that reinforce time-honored values while simultaneously partnering with others to nurture, sustain and improve patient care by addressing system issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 57 publications
(86 reference statements)
0
38
0
Order By: Relevance
“…Because it highlighted discordances between individual physicians’ goals to build therapeutic relationships with their patients, and prevailing system barriers and bureaucratic requirements, the study suggests the need for transforming organizational culture to make it more sustaining of humanistic practice. Strategies to reinforce the humanistic and relational aspects of care and their alignment with an organization’s values 12 , 23 , 27 , 38 , 39 , 41 , 42 , 44 46 are needed if an organizational culture of humanism is to flourish. 43 , 47 – 49 …”
Section: Discussionmentioning
confidence: 99%
“…Because it highlighted discordances between individual physicians’ goals to build therapeutic relationships with their patients, and prevailing system barriers and bureaucratic requirements, the study suggests the need for transforming organizational culture to make it more sustaining of humanistic practice. Strategies to reinforce the humanistic and relational aspects of care and their alignment with an organization’s values 12 , 23 , 27 , 38 , 39 , 41 , 42 , 44 46 are needed if an organizational culture of humanism is to flourish. 43 , 47 – 49 …”
Section: Discussionmentioning
confidence: 99%
“…While bio-psycho-social-spiritual models of patient care have been described [ 22 , 23 ], implementing such models in clinical practice remains a challenge. Recognized challenges include time constraints, work-related and personal stress, organizational culture, and episodic burnout [ 24 ]. Burnout impairs the quality of patient care through clinician detachment from their work [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The humanistic behaviours and attitudes reported by clinicians in our study helped them feel connected to patients and their families, and to learners. This research adds to the discourse around the notion that humanism may reduce burnout and enhance patient care through helping clinicians find meaning in their work and fostering resilience [ 24 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…8 In addition, Branch et al have reported on the interconnectedness of organizational and personal domains in building and maintaining well-being among health-care professionals. 9 A growing body of literature demonstrates that mindfulness-based interventions, including mind-body medicine skills, support the well-being of health-care professionals. 10 Mindfulness practices such as meditation are known to balance the autonomic nervous system and promote neurophysiologic changes in the hypothalamic-pituitary axis that among other effects also enhance focus and calm.…”
Section: Introductionmentioning
confidence: 99%